2015
DOI: 10.1021/ml500511m
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography to Elucidate Pharmacokinetic Differences of Regioisomeric Retinoid X Receptor Agonists

Abstract: RXR partial agonist NEt-4IB (2a, 6-[ethyl-(4-isobutoxy-3-isopropylphenyl)amino]pyridine-3-carboxylic acid: EC50 = 169 nM, E max = 55%) showed a blood concentration higher than its E max after single oral administration at 30 mg/kg to mice, and repeated oral administration at 10 mg/kg/day to KK-A(y) mice afforded antitype 2 diabetes activity without the side effects caused by RXR full agonists. However, RXR full agonist NEt-3IB (1a), in which the isobutoxy and isopropyl groups of 2a are interchanged, gave a muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…The novel RXR partial agonist NEt-4IB has a maximum 55% RXR efficacy compared with full agonists in a luciferase reporter gene assay, and 28 consecutive days’ administration of NEt-4IB resulted in no significant adverse events [14]. Furthermore, we have investigated the pharmacokinetics of NEt-4IB in vivo by positron emission tomography (PET) and revealed an increase in radioactivity in PET imaging of the lung [15]. …”
Section: Introductionmentioning
confidence: 99%
“…The novel RXR partial agonist NEt-4IB has a maximum 55% RXR efficacy compared with full agonists in a luciferase reporter gene assay, and 28 consecutive days’ administration of NEt-4IB resulted in no significant adverse events [14]. Furthermore, we have investigated the pharmacokinetics of NEt-4IB in vivo by positron emission tomography (PET) and revealed an increase in radioactivity in PET imaging of the lung [15]. …”
Section: Introductionmentioning
confidence: 99%
“…One reason for this may be the poor CNS penetration of bexarotene in human patients (~low nM range) [113]. Notably, in mice the BBB is extremely permeable to bexarotene [115]. This finding raises a general cautionary issue regarding translation of drugs from rodents to humans.…”
Section: Antisense Oligonucleotide Therapymentioning
confidence: 99%
“…Molecule 39 (EC 50 = 169 nM) has antitype 2 diabetes activity with reduced side effects compared to full RXR agonists in animal models and gave a higher blood concentration than full agonist 33 , after oral administration . Kobayashi et al investigated the pharmacokinetic difference of 39 and 33 (compounds are regioisomers) by positron emission tomography (PET). PET images revealed that 39 was easily absorbed from the digestive tract and excreted slowly than 33 .…”
Section: Rxr Agonistsmentioning
confidence: 99%
“…108 Molecule 39 (EC 50 = 169 nM) has antitype 2 diabetes activity with reduced side effects compared to full RXR agonists in animal models and gave a higher blood concentration than full agonist 33, after oral administration. 108 Kobayashi et al 69 PET images revealed that 39 was easily absorbed from the digestive tract and excreted slowly than 33. The partial RXR agonist 39 may be a promising candidate for the treatment of PD and AD as well without the serious side effects caused by 2.…”
Section: Bexarotene-related Compoundsmentioning
confidence: 99%
See 1 more Smart Citation